Congenital contractile peripapillary staphyloma with rhegmatogenous retinal detachment - Cao, Xu-Sheng; Jonas, Jost B. (Retinal cases & brief reports, 2018)
Purpose: To describe the occurrence of a congenital contractile peripapillary staphyloma in association with a rhegmatogenous retinal detachment. - Methods: The clinical course of a 17-year-old patient with a contractile peripapillary staphyloma and undergoing pars plana vitrectomy for repair of an associated retinal detachment was studied. - Results: The left eye showed a peripapillary staphyloma which during the ophthalmoscopical examination revealed contractile movements after the presentation of a light stimulus to either eye. The contraction of the peripapillary staphyloma was not correlated with a Valsalva maneuver, neck venous compression, forced lid closure, or respiratory movements. Because of a retinal detachment involving the inferior, nasal, and temporal retina, best-corrected visual acuity was 20/100. During pars plana vitrectomy under systemic anesthesia, the contractions of the peripapillary staphyloma subsided in the early phase of surgery, and reoccurred at approximately 80 minutes after the start of general anesthesia, when the posterior pole was touched with an aspiration syringe. - Conclusion: The etiology of the movements of the congenital peripapillary staphyloma in our patient may include a misbalance between intraocular pressure and orbital cerebrospinal fluid pressure or contractions of extraocular muscles. The observations may give information about the physiology and pathophysiology of the optic nerve head.
Gesehen am 27.03.2019